Pemahaman Pendidikan Islam Melalui Tafsir Ayat-Ayat Ilmu Pengetahuan Dalam Kitabullah - Shifa Azzahra; Sri Mulyani; Tsania Tazlila Warda; Revi Yulianti; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
Education is closely related to knowledge and science. Therefore, it is important to understand education from the concept of knowledge. In that context, in order to understand the concept of education in Islam, we must examine the verses of the Qur’an which talk about knowledge and knowledge. The aim of this research is to reveal the educational values contained in verses related to science based on verse interpretations. The method of writing this article is to collect verses from the Qur’an thematically on certain topics and arrange them based on the period of revelation. The results of this research show that science is a process that is carried out using methods and produces new knowledge that is systematic and structured and used as direction for humans. There are three laws regarding studying various types of science: obligatory, sunnah and haram. The application of science can be practiced as early as possible in formal education in harmony with the verses of the Qur’an.